2005
DOI: 10.1243/030932405x7818
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue life improvement of threaded connections by cold rolling

Abstract: Failures in drillstring threaded connections continue to afflict the oil industry at a cost of millions of dollars per year. In an attempt to reduce these failures the industry has generally adopted the fatigue-life-enhancing technique of cold rolling the threaded connections which act as stress concentrations. However, this beneficial process is only specified as optional in the industry standards, and where it is performed there is very little detail provided about this important process. This paper describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The fatigue crack growth ratio or crack aspect ratio for the stitch rolled specimens remained relatively constant throughout the section thickness. The aspect ratio at failure (through‐thickness) was significantly less than the previously tested specimens 12 Figure 13. illustrates the relationship between crack length and crack depth for the pin connectors.…”
Section: Test Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…The fatigue crack growth ratio or crack aspect ratio for the stitch rolled specimens remained relatively constant throughout the section thickness. The aspect ratio at failure (through‐thickness) was significantly less than the previously tested specimens 12 Figure 13. illustrates the relationship between crack length and crack depth for the pin connectors.…”
Section: Test Resultsmentioning
confidence: 63%
“…Results from earlier tests 12 had indicated that surface crack growth may be influenced by the levels of residual compressive surface stress introduced from cold rolling. Fig.…”
Section: Test Resultsmentioning
confidence: 99%
See 3 more Smart Citations